Influence Of Post-Harvest Calcium Chloride Treatments On Physico-Chemical And Sensory Attributes Of Pear Cv. ‘bartlett’ Under Ambient Storage Conditions (Applied Biological Research, 2017)
Freshly harvested pear fruits were treated with different CaCl2 concentrations  (1, 2, 3 and 4%) for 10, 20 and 30 min,respectively, for each concentration and  dipping time changes in the activity of cell wall degrading pectic enzymes viz., pectin methyl esterase (PME), polygalacturonase (PG), quality parameters viz., fruit firmness, TSS: acid ratio, respiration rate, physiological loss in weight  (PLW) and sensory characteristics viz., colour, taste, texture and overall  acceptability were studied on different sampling dates (7, 10, 13, 16 and 19th day). PME activity, fruit respiration, PLW and sensory quality of fruits increased in all the treatments up to the climacteric peak of respiration which  appeared on 16th day of storage in the fruits treated with 4 % CaCl2 for 30 and  20 min and 3% CaCl2 for 30 min, and decreased thereafter. The activity of PG and TSS: acid ratio increased progressively during ripening of pear fruits. The  increase in PG activity closely followed decrease in fruit firmness, while the  activity of PG did not exactly match the respiration climacterics.
Keywords: CaCl2; enzyme firmness; fruit quality; pear; respiration